Queer Women with Disabilities — Intersections in Identity - Whitney, Chelsea (My University, 2005)
Until recently the sexuality of individuals with disabilities has largely been ignored or incorrectly assumed to be non-existent. Individuals with disabilities have a range of sexual orientations encompassing both heterosexual and queer identities. In what ways do individuals with disabilities construct their sexual orientation identity? How do women who identify as both disabled and queer develop their multiple identities? Do current models of lesbian identity development or models of disability identity development address the reality of queer women with disabilities identity? This project involved interviews with five queer women with disabilities in the Northwest to understand their subjective experiences of their identity and the process of its development. Interviews were audio-recorded, transcribed, and analyzed with Atlas.ti software. Both identity development models for disability and queer identity could be used to describe either women’s disability identity development or queer identity development. A combination of identity development models best fit these women’s life experiences. Implications for future theory and activism stemming from dual identities are discussed.
Undergraduate Thesis - Women Studies, University of Washington (2005).
Keywords: Identity Development; Lesbians; Bisexuals; Disability; Interviews